SCIATICA (Homoeopathy for All, 2022)
Approximately 80% of the population is plagued at one time or another by back pain, especially lower back pain. A common mistake is referring to any low back pain or radicular leg pain as sciatica. It is a clinical diagnosis based on the presence of radiating pain in one leg, with or without the associated neurological deficits. The lifetime incidence of this condition is estimated to be between 13% and 40%. Fortunately, the majority of cases resolve spontaneously with rest and correct medication.
Keywords: SCIATICA; medication; pain